Structural and electrochemical properties of mesoporous FeVO4 as a negative electrode for lithium‐ion battery. (11th May 2022) - Kakarla, Ashok Kumar; Narsimulu, D.; Patnam, Harishkumar Reddy; Shanthappa, R.; Yu, Jae Su
Summary: The approach to accomplishing long cycle solidity usually depends on the electrode materials in lithium‐ion batteries (LIBs). Herein, mesoporous FeVO4 (MFVO) nanostructures (NSs) were prepared via a simple hydrothermal method and post‐calcination using different concentrations of ethylenediaminetetraacetic acid (EDTA) chelating agent. The morphology, microstructure, and mesoporous nature of the as‐prepared samples were characterized by scanning electron microscope, transmission electron microscope, and Brunauer‐Emmett‐Teller analyses, respectively. The as‐obtained MFVO NSs were examined as a negative material for LIBs. The enhanced MFVO‐2 (0.2 g of EDTA) electrode provides an initial charge/discharge capacity of 2880 mA h g −1 /2707 mA h g −1 at 0.1 A g −1 . Even after 100 cycles, it displays a superior specific discharge capacity of 906 mA h g −1 . Furthermore, the MFVO‐2 electrode exhibits a high‐rate performance with a steady reversible capacity. As a result, the porosity and density of nanorod‐like morphologies are significant factors in their electrochemical performances. The outstanding electrochemical effects of MFVO NSs may be suggested as a prospective anode material for enhanced LIBs.